Quality of work life, selected socio-demographic profile and job performance of nursing faculty in state universities in Region IV-A - De Vera, Lenila A. (Thesis -- (Masters in Arts in Nursing). -- University of the Philippines Manila.)
The study aimed to find a correlation between the Quality of Work Life (QWL), selected socio-demographic profile and the job performance of the nursing faculty in various state universities in Region IV-A. It utilized a non-experimental descriptive-correlational research design. The data for the study was analyzed using multiple statistical procedures: mean standard deviation, Spearman's rank- order correlation rho, Chi-square test and Pearson r. Simultaneous Multiple Regression was used to determine the predictors of Job Performance among Quality of Life Indicators.
The study was conducted among the 113 respondents, majority of whom were female (79.6%) and married (63.7%). The mean age is 37.2 with SD of 10.53. Among the four QWL factors, respondents put a high regard in Home Work Interface (M=3.24, SD=0.37) followed by Job and Career Satisfaction (M=3.10, SD=0.41), while Safe and Healthy Work Condition was rated lowest (M=2, 90, SD=0.41). Among their functions, the Deans and RLE supervisors rated the Job Performance of the nursing faculty as very good in all areas with the highest in Curriculum and Instruction (M=3.91, SD=.041), followed by Research (M=3.20, SD=.90) and Extension (M=3.23, SD=.97) as the least. There is no significant relationship between Curriculum and Instruction and Extension on all the socio-demographic. Significant relationship was shown between Research and civil status (x²=13.72, p<.05) and length of experience (r=.195 <.05) but not with age and sex. Among the four QWL factors, Control at Work and Home Work Interface significantly predicted Curriculum Instruction, f (4, 108) = 3.46, p<.05. Only Safe and Healthy Work Condition (p<.05) made significant contributions to Research while none of the QWL factors made significant contributions to Extension.
The study presented relationships between Quality of Work life and Job Performance of nursing faculty. It showed that not all quality of life aspects had significant relationship with job performance as supported by the three latter findings on which predictive models were used. There could be other factors that might contribute to the quality of work life.
Based on the findings of the study, the following are suggested/recommended. Administrators should encourage more faculty involvement in Extension. This may be accomplished by reducing the teaching workload to allow more time for Extension work. Benefit packages can be developed by using the findings of this study to promote and improve the QWL and productivity of nursing faculty in state universities in Region IV-A, and lastly, results of this study suggest the conduct of further research to explore other factors that contribute to the Quality of Work life of the nursing faculty in state universities in Region IV-A.
Keywords: Faculty, Nursing; Quality of Work Life